2022
DOI: 10.3390/plants11010133
|View full text |Cite
|
Sign up to set email alerts
|

Use of Biostimulants: Towards Sustainable Approach to Enhance Durum Wheat Performances

Abstract: The use of biostimulant (BS) holds a promising and environmental-friendly innovation to address current needs of sustainable agriculture. The aim of the present study is twofold: (i) assess the potential of durum wheat seed coating with microbial BS (‘Panoramix’, Koppert), a mix of Bacillus spp., Trichoderma spp., and endomycorrhiza, compared to two chemical products (‘Spectro’ and ‘Mycoseeds’) through germination bioassay, pot and field trials under semi-arid conditions, and (ii) identify the most effective m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…İD İD Vijayakumari et al, 2016), chitosan (Rashidi et al, 2020), salicylic acid (Hayat et al, 2010) and many other known and newly identified compounds (Valluru et al, 2016;Ashour et al, 2021;Sheikhalipour et al, 2021;Ayed et al, 2022) are reported to enhance growth, development and stress tolerance levels in crops. Therefore, priming, foliar spraying, or other external field applications of these compounds are of great importance for agricultural sustainability (Singh et al, 2015;Pawar and Laware, 2018;Zulfiqar, 2021).…”
Section: Orcid Id (By Author Order)mentioning
confidence: 99%
See 1 more Smart Citation
“…İD İD Vijayakumari et al, 2016), chitosan (Rashidi et al, 2020), salicylic acid (Hayat et al, 2010) and many other known and newly identified compounds (Valluru et al, 2016;Ashour et al, 2021;Sheikhalipour et al, 2021;Ayed et al, 2022) are reported to enhance growth, development and stress tolerance levels in crops. Therefore, priming, foliar spraying, or other external field applications of these compounds are of great importance for agricultural sustainability (Singh et al, 2015;Pawar and Laware, 2018;Zulfiqar, 2021).…”
Section: Orcid Id (By Author Order)mentioning
confidence: 99%
“…There have been several studies and applications to enhance salt stress tolerance in tomato (Cuartero and Fernandez-Munoz, 1999;Ashraf and Harris, 2004;Flowers, 2004;Foolad, 2004;Mayak et al, 2004;Munns, 2011;Shahbaz et al, 2012;Machado and Serralheiro, 2017), however, there is still a significant need for practical applications to reduce or eliminate the destructive effects of salt stress on tomato production. Foliar application of biostimulants would be an easy and cheap strategy to mitigate stress levels on crops (Ayed et al, 2022). Therefore, this study aimed to 1) evaluate the effect of chitosan foliar spraying on growth and development, and 2) the physiological parameters of tomato (S. lycopersicum L.) under salt-stressed conditions.…”
Section: Orcid Id (By Author Order)mentioning
confidence: 99%
“…Over the time, various researchers have classified biostimulants into nine broad categories including seaweeds and plant extracts, complex organic materials (obtained from sewage sludge extracts, composts, manure urban and agro-industrial waste products), humic substances, antitranspirants (kaolin and polyacrylamide), chitin and chitosan derivatives, elements (Al, Co, Se, Na, and Si), hydrolyzed proteins, nitrogen-containing compounds and microbial inoculants ( Colla and Rouphael, 2020 ; Teklić et al., 2021 ; Franzoni et al., 2022 ; Monteiro et al., 2022 ). Out of this wide category, microbial-based biostimulants including plant growth-promoting bacteria ( Bacillus, Serratia, Arthrobacter, Pseudomonas, Rhodococcus, Enterobacter, Ochrobactrum, Acinetobacter, Azospirillum, Rhizobium, Streptomyces and Stenotrophomonas ) have surfaced as highly valuable and inexpensive agricultural input for improving plant yield ( Orozco-Mosqueda et al., 2020 ; Baltazar et al., 2021 ; Miceli et al., 2021 ; Ayed et al., 2022 ; Fadiji et al., 2022 ). These microbiome based biostimulants trigger plant growth through solubilization of minerals (Zn, P and K), nitrogen fixation, production of phytohormones like indole-3-acetic acid (IAA), abscisic acid (ABA), ethylene (ET), cytokinin (CK), jasmonic acid (JA), secondary metabolites (siderophores, N-acyl homoserine lactone, lipopeptides, rhamnolipids, cyclic lipopeptides), enzymes (chitinases, cellulose, protease, glucanase etc.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, Brazil is considered the largest producer of soybeans, with an estimated production for 2023 of 151. 5 Considering the signi cant representation of soybeans, phytotechnical studies are necessary to enhance its productivity, and seedling vigor is important characteristic in the formation for production stand. In this sense, seeds treatment with biostimulant or biofertilizer products is a promising practice, as it contributes to seed physiology, stimulating germination, emergence and vigor of seedlings (Silva et In Brazil, Ministry of Agriculture and Livestock published Decree No.…”
Section: Introductionmentioning
confidence: 99%